2022
DOI: 10.1039/d1tc05906h
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional class of thermally activated delayed fluorescent emitters that display pure blue, near-IR, circularly polarized luminescence and multifunctional behaviour for highly efficient and stable OLEDs

Abstract: Thermally activated delayed fluorescence (TADF) emitters delivering an ability to harvest both electro-generated singlet and triplet excitons have resulted in faster radiative decay, saturated color purity, high photoluminescence quantum yield...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 94 publications
0
18
0
Order By: Relevance
“…Further, ISC and RISC rate constants calculated from PLQY and lifetime values of the prompt and delayed components were estimated to be k ISC = 7.5 × 10 6 s −1 , 1.53 × 10 6 s −1 , 1.25 × 10 6 s −1 , 0.75 × 10 6 s −1 and k RISC = 1.47 × 10 5 s −1 , 0.24 × 10 5 s −1 , 0.46 × 10 5 s −1 , 0.48 × 10 5 s −1 , for BT2O x Cz ( x = 3–6) respectively (summarized in Table S1 † ). 43 To obtain clear insights into phosphorescence emission at the molecular level, including elimination of the molecular aggregation effect and to restrict non-radiative motion, a set of control experiments were conducted on spin-coated films after doping all the BT2O x Cz WLEs at 0.5 wt% and 5 wt% concentration into PMMA under inert conditions using dry toluene. The phosphorescence spectrum in low concentrated films (0.5%) exhibited three distinct peaks located at 450 nm (TADF), 545 nm (fast RTP, τ av = ∼80 µs) and 700 nm (slow RTP, τ av = ∼2.5 ms) covering the entire visible range ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further, ISC and RISC rate constants calculated from PLQY and lifetime values of the prompt and delayed components were estimated to be k ISC = 7.5 × 10 6 s −1 , 1.53 × 10 6 s −1 , 1.25 × 10 6 s −1 , 0.75 × 10 6 s −1 and k RISC = 1.47 × 10 5 s −1 , 0.24 × 10 5 s −1 , 0.46 × 10 5 s −1 , 0.48 × 10 5 s −1 , for BT2O x Cz ( x = 3–6) respectively (summarized in Table S1 † ). 43 To obtain clear insights into phosphorescence emission at the molecular level, including elimination of the molecular aggregation effect and to restrict non-radiative motion, a set of control experiments were conducted on spin-coated films after doping all the BT2O x Cz WLEs at 0.5 wt% and 5 wt% concentration into PMMA under inert conditions using dry toluene. The phosphorescence spectrum in low concentrated films (0.5%) exhibited three distinct peaks located at 450 nm (TADF), 545 nm (fast RTP, τ av = ∼80 µs) and 700 nm (slow RTP, τ av = ∼2.5 ms) covering the entire visible range ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As known, structural isomers are different compounds that have the same molecular formula but the atoms are attached in distinct ways by covalent bonds, which have signicant effects on chemical and physical properties. 18,19 Isomers with different structures can induce geometric and electronic structure changes in molecules. 20 In the past decade, much attention has been paid to the development of new types of electron donors and acceptors to construct highly efficient TADF molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] The numerous practical uses of near-infrared (NIR) emission motivate the scientific community to create materials, designs, and physical mechanisms for effective NIR TADF OLEDs. 10,11 Regarding exciton consumption and efficiency, NIR TADF emitter development continues to lag behind visible range TADF emitters. 12 Thus, there remains an opportunity for new molecular approaches and in-depth photophysical investigations for stable and efficient NIR TADF OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Carbazole, diphenylamine (DPA), triphenylamine (TPA), phenoxazine, acridine, and their derivatives are the most often utilized donor moieties in NIR TADF molecules. 11 Similarly, dibenzo (a,c) phenazene-3,6 dicarbonitrile (PZCN), acetylacetonate boron difluoride, quinoxaline 6,7-dicarbonitrile (QCN) and phenanthrene derivatives have been used as acceptors. 12,39 Wang et al reported the first successful example of a NIR TADF emitter (TPA-DCPP) in 2015.…”
Section: Introductionmentioning
confidence: 99%